Analysis of clinical efficacy of sacral magnetic stimulation for the treatment of detrusor underactivity - Pan, Huixian; Tang, Chenhao; Song, Chen; Li, Junhua (Frontiers in Neurology, 2025)
ObjectiveThe objective of this study was to investigate the effectiveness and safety of sacral magnetic stimulation (SMS) in the management of detrusor underactivity (DU).MethodsWe retrospectively analyzed 66 patients with detrusor underactivity treated at Hangzhou Third People’s Hospital from January 2020 to October 2024, divided into two groups (33 cases each). Both groups had confirmed detrusor underactivity via urodynamic studies. The control group received conventional treatment (medication, catheterization, bladder training), while the observation group received SMS therapy. Urination diaries, urodynamic parameters and self-rating anxiety scale (SAS) were collected before and after the 4-week treatment to evaluate SMS efficacy and safety.ResultsAll patients in the observation group completed the course of sacral magnetic stimulation without experiencing any serious complications. After treatment, the observation group showed a significant reduction in the number of daily urinations, nocturnal urinations, SAS score and residual urine volume (RUV) (p < 0.05) compared with the control group. There was no statistically significant difference in maximum cystometric capacity (MCC) (p > 0.05). However, improvements were observed in SAS score, Detrusor Pressure at Maximum Flow (Pdet), Bladder Contractility Index (BCI), Maximum urinary Flow Rate (Qmax) and Average Urinary Flow Rate (Qavg) (p < 0.05). The effective rate in the observation group was 78.78%, significantly higher than that in the control group (p < 0.05). Although there was a slight decrease in the effective rate during the 6-month follow-up, the difference was not statistically significant (p > 0.05).ConclusionIn conclusion, sacral magnetic stimulation therapy has demonstrated effectiveness in improving urinary function in patients with detrusor underactivity while maintaining a high level of safety.